2013
DOI: 10.1016/j.cub.2013.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Cellular Plasticity in the Pancreas

Abstract: SUMMARY Obese individuals exhibit an increase in pancreatic β-cell mass; conversely, scarce nutrition during pregnancy has been linked to β-cell insufficiency in the offspring (reviewed in [1, 2]). These phenomena are thought to be mediated mainly through effects on β-cell proliferation, since a nutrient sensitive β-cell progenitor population in the pancreas has not been identified. Here, we employed the FUCCI (Fluorescent Ubiquitination-based Cell Cycle Indicator) system to investigate β-cell replication in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
110
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 44 publications
5
110
0
Order By: Relevance
“…In summary, our data are consistent with a model whereby the glucagon/GLP-1 signaling pathway works through two routes to elicit new β cell formation: (1) non-autonomously through stimulation of hepatic glucose production, which can stimulate β cell formation from naïve duct-associated progenitor cells (Guillemain et al, 2007;Ninov et al, 2013); and (2) autonomously within the α cell compartment to regulate α cell mass and cell identity (Fig. 6L).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In summary, our data are consistent with a model whereby the glucagon/GLP-1 signaling pathway works through two routes to elicit new β cell formation: (1) non-autonomously through stimulation of hepatic glucose production, which can stimulate β cell formation from naïve duct-associated progenitor cells (Guillemain et al, 2007;Ninov et al, 2013); and (2) autonomously within the α cell compartment to regulate α cell mass and cell identity (Fig. 6L).…”
Section: Discussionsupporting
confidence: 72%
“…We have investigated the origins of regenerating pancreatic β cells in this zebrafish β cell ablation model using two approaches: a Crelox-based genetic lineage-tracing approach that indelibly marks endocrine cells with temporal precision; and a non-genetic celltracing approach that marks quiescent, differentiated endocrine cells . Using these approaches, we distinguished two sources of new β cells: a ventral pancreatic bud-derived source, which may include the 'naïve' duct-associated progenitor cells that have been described previously (Wang et al, 2011;Ninov et al, 2013); and non-β endocrine cells (α cells in particular) that transdifferentiate into β cells. Thus, we have shown for the first time the spontaneous facultative conversion of α cells into β cells in an organism other than mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is proposed that the hyperactivated ␤-cells replicate cells autonomously (9), existing data cannot rule out a paracrine mechanism. By manipulating membrane depolarization at a stage when ␤-cells are refractory to replication (33,39), we revealed a cell nonautonomous role of hyperactivated ␤-cells in ␤-cell genesis. It is tantalizing to speculate that the same factor(s) may be secreted from hyperactivated ␤-cells in adult mammals and contribute to the ensuing ␤-cell replication.…”
Section: Discussionmentioning
confidence: 99%
“…These results provide models that must then be tested in the more complicated and generally used systems. Because zebrafish also generate ␤-cells through replication at later stages (36,39), it will be of great interest to explore these systems to determine if the sensor system identified here functions universally in ␤-cell genesis or whether this is model specific.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish pancreas is a highly plastic organ, containing β-cells and β-cell progenitors that respond to metabolic and regenerative cues (Ninov et al, 2013). Using multicolor lineage tracing, Sumeet Singh (Ninov laboratory, CRT, Dresden, Germany) showed that the developmental origin, replicative history and functionality of β-cells within zebrafish islets are highly heterogeneous.…”
Section: Model Systems To Study Stemness and Cellular Plasticitymentioning
confidence: 99%